Desain dan Pengembangan Transfer Case untuk Kendaraan Multi Guna Kapasitas Angkut 750 Kilogram - Asep Indra Komara; Panji Mufti Ali; Antonius Adi Soetopo (Manutech : Jurnal Teknologi Manufaktur, 2020)
The Automotive Power Train Development Center (P3TO) POLMAN Bandung aims to develop utility vehicles for agricultural and plantation areas with a loading capacity of 750 kg. One of the studies focuses on the design and development of the transfer case transmission system, an additional unit in the transmission system for distributing power from the engine to the wheels and production machines through Power Take-Off (PTO). The purpose of this research is to produce a transfer case design that provides large power output, reliable, safe, and cheap. The engineering process is preceded by studying on existing construction then modifying and designing it to meet demands by applying the Pahl & Beitz methodology consisting of planning and clarifying tasks, making a list of demands, making basic concepts, designing transfer cases, and validating designs. The main evaluation criteria such as vehicle operations in all-terain, engine, gearbox, and vehicle speed were observed. The results were also validated using three methods, namely theoretical, KISSsoft software, and finite element simulation in solids work. This research produced a transfer case design of 1.8 rations with a size of 461 mm x 433 mm x 223 mm and a weight of 25 kg. All gear and shaft components are able to withstand the load that occurs in the transfer case due to operational, engine, and production machine tools.